Corporate social responsibility in tourism: the case of Zoomarine Algarve - Contreiras, J. P.; Machado, V.; Duarte, A. P. (Tourism and Management Studies, 2016)
This study had a threefold purpose. First, it sought to examine the opinion of three important stakeholders – employees, visitors and members of the local community – about the corporate social responsibility (CSR) practices of the theme park, Zoomarine Algarve. Second, this study evaluated the perceptions of the public regarding the impact of the company’s activities on regional development and environmental awareness. Last, the study sought to understand if stakeholders’ opinions regarding this company’s engagement in CSR practices are related to the impacts attributed to Zoomarine Algarve’s regular functions. The methodology comprised quantitative research based on a survey administered to convenience samples of the target groups (n = 405). The results reveal that stakeholders have an extremely positive view of the theme park’s engagement in CSR practices and feel that it contributes significantly to regional development, as well as to raising the environmental awareness of visitors and local communities. The findings also show that perceptions of CSR engagement are positively related with perceived impacts.